2017
DOI: 10.1002/mc.22716
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants in the metzincin metallopeptidase family genes predict melanoma survival

Abstract: Metzincins are key molecules in the degradation of the extracellular matrix and play an important role in cellular processes such as cell migration, adhesion, and cell fusion of malignant tumors, including cutaneous melanoma (CM). We hypothesized that genetic variants of the metzincin metallopeptidase family genes would be associated with CM-specific survival (CMSS). To test this hypothesis, we first performed Cox proportional hazards regression analysis to evaluate the associations between genetic variants of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
(90 reference statements)
0
5
0
Order By: Relevance
“…Some studies have indicated that high expression of MMP16 is associated with the proliferation, migration, and invasion of cutaneous squamous cell carcinoma cells [ 51 ], while knockdown of MMP16 could inhibit cell proliferation and invasion in chordoma cells [ 11 ]. Moreover, some variations in MMP16 have been found to be associated with different types of diseases [ 52 , 53 ]. In our study, MMP16 was found to be upregulated in UVM, and high expression was associated with shorter OS and DFS.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have indicated that high expression of MMP16 is associated with the proliferation, migration, and invasion of cutaneous squamous cell carcinoma cells [ 51 ], while knockdown of MMP16 could inhibit cell proliferation and invasion in chordoma cells [ 11 ]. Moreover, some variations in MMP16 have been found to be associated with different types of diseases [ 52 , 53 ]. In our study, MMP16 was found to be upregulated in UVM, and high expression was associated with shorter OS and DFS.…”
Section: Discussionmentioning
confidence: 99%
“…ADAMTS3 is involved in the alteration of osteosarcoma matrices [ 25 ], and the single nucleotide polymorphism (SNP) of the ADAMTS3 gene is an independent prognostic biomarker for cutaneous melanoma [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, other regulatory mechanisms of MMP-9 expression are mediated by MMP-9 allelic variation (rs3918251GG (A>G) and by the over-expression of SOX4 responsible for the concomitant up-regulation of MMP-2/9 and NF-κB/p65 and, consequently, for a more aggressive tumor phenotype [78,79].…”
Section: Mmp-9 Functions and Regulation In Melanomamentioning
confidence: 99%